Gastroprotective Effect of Ginger Rhizome (Zingiber officinale) Extract: Role of Gallic Acid and Cinnamic Acid in H+, K+-ATPase/H. pylori Inhibition and Anti-Oxidative Mechanism. (23rd June 2011) - Nanjundaiah, Siddaraju M.; Annaiah, Harish Nayaka Mysore; Dharmesh, Shylaja M.
Abstract : Zinger officinale has been used as a traditional source against gastric disturbances from time immemorial. The ulcer-preventive properties of aqueous extract of ginger rhizome (GRAE) belonging to the family Zingiberaceae is reported in the present study. GRAE at 200 mg kg −1 b.w. protected up to 86% and 77% for the swim stress-/ethanol stress-induced ulcers with an ulcer index (UI) of 50 ± 4.0/46 ± 4.0, respectively, similar to that of lansoprazole (80%) at 30 mg kg −1 b.w. Increased H +, K + -ATPase activity and thiobarbituric acid reactive substances (TBARS) were observed in ulcer-induced rats, while GRAE fed rats showed normalized levels and GRAE also normalized depleted/amplified anti-oxidant enzymes in swim stress and ethanol stress-induced animals. Gastric mucin damage was recovered up to 77% and 74% in swim stress and ethanol stress, respectively after GRAE treatment. GRAE also inhibited the growth of H. pylori with MIC of 300 ± 38 μ g and also possessed reducing power, free radical scavenging ability with an IC50 of 6.8 ± 0.4 μ g mL −1 gallic acid equivalent (GAE). DNA protection up to 90% at 0.4 μ g was also observed. Toxicity studies indicated no lethal effects in rats fed up to 5 g kg −1 b.w. Compositional analysis favored by determination of the efficacy of individual phenolic acids towards their potential ulcer-preventive ability revealed that between cinnamic (50%) and gallic (46%) phenolic acids, cinnamic acid appear to contribute to better H +, K + -ATPase and Helicobacter pylori inhibitory activity, while gallic acid contributes significantly to anti-oxidant activity.